К вопросу о питании карпатского медведя бурого (Ursus arctos L.) - Слободян, А.А. (Вестник зоологии, 1975)
In the studied territory of the Solotvin timber combine of the combine «Prikarpatles> the food of Ursus arctos L. consists primarily of vegetative components (61.8%) with berries and fruits amounting to 30.9%. In animal food (38.2%) the mammals (21.1%) and insects (10.4%) dominate. As Ursus arctos sometimes do not hibernate in dens their winter ration is indicated.